Parenting Styles and Their Impacts on Children in @dailyjour’s TikTok - Chiara Aurelia Priscilla Parera; Theophilus Joko Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2025)
This paper aims to analyze the types of parenting styles and their impacts in @dailyjour’s TikTok, the story of a mother educating her children in everyday life through her roleplay. The applied theories are the types and impacts of parenting styles by Diana Baumrind. The types are authoritarian, authoritative, and permissive. The impacts for the authoritarian are discontent, withdrawal, and distrustful. The impacts for the authoritative are content, self-reliance, and self-control. The impacts for the permissive are a lack of self-reliance and a lack of self-control. The data is based on the mother's words towards her children and their potential impacts on the children. The findings show that the authoritarian parenting style indicates totally negative impacts, the authoritative indicates the most positive impacts, and the permissive indicates the least positive impacts. In conclusion, the mother's various ways of parenting influence the children'